Nanobubbles: Graphene Nanobubbles: A New Optical Nonlinear Material (Advanced Optical Materials 6/2015). Issue 6 (June 2015) - Bao, Qiaoliang; Chen, Jianqiang; Xiang, Yuanjiang; Zhang, Kai; Li, Shaojuan; Jiang, Xiaofang; Xu, Qing‐Hua; Loh, Kian Ping; Venkatesan, T.
<x xml:space="preserve">Abstract</x> To overcome optical path length limitations of atomically thin 2D films, all‐optical switching is demonstrated in graphene nanobubbles. On page 744, Q. Bao, K. P. Loh, T. Venkatesan, and co‐workers show how thermally stressing graphene leads to an array of nanobubbles, allowing a large optical phase shift due to their vertical side walls and added curvature.